Urinary and exhaled biomarkers of exercise‐induced bronchoconstriction in atopic asthmatic children. Issue 9 (19th June 2019) - Barreto, Mario; Capi, Matilde; Lionetto, Luana; Caiazzo, Ilaria; Salerno, Gerardo; Cardelli, Patrizia; Simmaco, Maurizio; Villa, Maria Pia
Abstract: Background: Exercise‐induced bronchoconstriction (EIB) reflects poor asthma control. Assessing noninvasive biomarkers associated with EIB could help to monitor patients in the pediatric age. Aims: To test exhaled and urinary biomarkers for assessing EIB in atopic asthmatic children. Methods: In 45 atopic patients (11.1 ± 1.8 years, 25 males) we measured the fractional exhaled nitric oxide (FENO ), its alveolar (CaNO), and bronchial (J'awNO) components corrected for the trumpet shape of the airways and axial NO diffusion (TMAD), concentrations of urinary adenosine and 8‐hydroxy‐2'‐deoxyguanosine (8‐OxodG), blood eosinophils count, total immunoglobulin E, skin prick tests, and baseline spirometry before a treadmill exercise challenge. Forty healthy control subjects participated solely to baseline measurements. Results: Patients yielded higher FENO and urinary adenosine concentrations than healthy controls. After the challenge, 18 patients (40%) had EIB; these patients had higher levels of CaNO, CaNO TMAD, and urinary adenosine than patients without EIB. Baseline spirometry, FENO, JawNO, JawNO TMAD, urinary 8‐OxodG, allergy, and blood eosinophil counts were found similar in both groups. In multiple linear regression, the fall in FEV1 was explained by CaNO TMAD, urinary adenosine and blood eosinophil count, whereas the fall in FEF25‐75 was explained by CaNO TMAD and blood eosinophil count. Both CaNO TMAD ≥10.5 ppb and urinary adenosine ≥406 nmol/mmol Cr predicted a fall in FEV1 ≥10%, while only CaNO TMAD ≥10.5 ppb predicted a fall in FEF25‐75 ≥26%. Conclusion: Concentrations of peripheral airway NO are complementary with urinary adenosine for assessing EIB and promising tools of asthma control in pediatric patients with the atopic phenotype.